Trauma; Psychosis and Posttraumatic Stress Disorder - Kate V. Hardy (Frontiers Research Topics, 2017)
There is abundant evidence showing a strong association between trauma exposure, psychotic symptoms, and posttraumatic stress disorder (PTSD). Early trauma exposure contributes to the formation of psychotic symptoms and the development of psychotic disorders or severe mental illnesses such as schizophrenia, bipolar disorder, and treatment-refractory major depression. Furthermore, among persons with psychotic disorders, multiple traumatization over the lifetime is common, due to factors such as social stigma, the criminalization of severe mental illness, and increased vulnerability to interpersonal victimization. In addition to these factors is the traumatic nature of experiencing psychotic symptoms and coercive treatments such as involuntary hospitalization and being placed in seclusion or restraints. Not surprisingly, these high rates of trauma lead to high rates of PTSD in people with psychotic disorders, which are associated with more severe symptoms, worse functioning, and greater use of acute care services. In addition to the impact of trauma on the development of psychotic disorders and comorbid PTSD, traumatic experiences such as childhood sexual and physical abuse can shape the nature of prominent psychotic symptoms such as the content of auditory hallucinations and delusional beliefs. Additionally, traumatic experiences have been implicated in the role of 'stress responsivity' and increased risk for transition to psychosis in those identified as being at clinical high risk of developing psychosis. Finally, although the diagnostic criteria for PTSD primarily emphasize the effects of trauma on anxiety, avoidance, physiological over-arousal, and negative thoughts, it is well established that PTSD is frequently accompanied by psychotic symptoms such as hallucinations and delusions that cannot be attributed to another DSM-V Axis I disorder such as psychotic depression or schizophrenia. Understanding the contribution of traumatic experiences to the etiology of psychosis and other symptoms can inform the provision of cognitive behavioral therapy for psychosis, including the development of a shared formulation of the events leading up to the onset of the disorder, as well as other trauma-informed treatments that address distressing and disabling symptoms associated with trauma and psychosis. Until recently the trauma treatment needs of this population have been neglected, despite the high rates of trauma and PTSD in persons with psychotic disorders, and in spite of substantial gains made in the treatment of PTSD in the general population. Fortunately, progress in recent years has provided encouraging evidence that PTSD can be effectively treated in people with psychotic disorders using interventions adapted from PTSD treatments developed for the general population. In contrast to clinician fears about the untoward effects of trauma-focused treatments on persons with a psychotic disorder, research indicates that post-traumatic disorders can be safely treated, and that participants frequently experience symptom relief and improved functioning. There is a need to develop a better understanding of the interface between trauma, psychosis, and post-traumatic disorder. This Frontiers Research Topic is devoted to research addressing this interface.